Пошаговое объяснение:
1) = a + 5a - 3b - a + 6 = 5a - 3b + 6
2) = 4b - a - b + 7a + 9 = 6a + 3b + 9
3) = 3a - 17a + 6b - 8a - 1 = -22a + 6b - 1
4) = 6b + (3b - 2a - 5b) = 6b + 3b - 2a - 5b = -2a + 4b
1) 7x - 4 = x - 16
7x - x = -16 + 4
6x = -12
x = -12:6
x = -2
2) 13 - 5x = 8 - 2x
5x - 2x = 13 - 8
3x = 5
x = 5:3
x = 1 2/3
3) 4y + 15 = 6y + 17
6y - 4y = 15 - 17
2y = -2
y = -2:2
y = -1
4)5x + (3x - 7) = 9
5x + 3x - 7 = 9
8x - 7 = 9
8x = 9 + 7
8x = 16
x = 16 : 8
x = 2
5) 3y - (5 - y) = 11
3y - 5 + y = 11
4y - 5 = 11
4y = 11 + 5
4y = 16
y = 16 : 4
y = 4
Пусть x = AB
ABH - прямоугольный треугольник
AH = x-6
По теореме Пифагора:
x^2 = (x-6)^2 + 64
x=8.3
ответ: AB = 8.3